Multiple Mouse Text Entry for Single-Display Groupware - Amershi, Saleema; Morris, Meredith Ringel; Moraveji, Neema; Balakrishnan, Ravin; Toyama, Kentaro (CSCW, 2010)
A recent trend in interface design for classrooms in developing regions has many students interacting on the same display using mice. Text entry has emerged as an important problem preventing such mouse-based singledisplay groupware systems from offering compelling interactive activities. We explore the design space of mouse-based text entry and develop 13 techniques with novel characteristics suited to the multiple mouse scenario. We evaluated these in a 3-phase study over 14 days with 40 students in 2 developing region schools. The results show that one technique effectively balanced all of our design dimensions, another was most preferred by students, and both could benefit from augmentation to support collaborative interaction. Our results also provide insights into the factors that create an optimal text entry technique for single-display groupware systems.
Best Paper Honorable Mention